Amniotic Band Syndrome with CTEV and Meningocele: A Rare Case Report - Shrestha, Sandeep; Thani, Kamal Prasad; Gautam, Uttara; Bhattarai, Nishan; Shrestha, Annie; Keshari, Munna; Sainju, Akina; Lamichhane, Santosh; Thapaliya, Pooja (Journal of Karnali Academy of Health Sciences, 2023)
Amniotic band syndrome (ABS) is a group of rare congenital abnormalities caused by wrapping of parts of the foetus by fibrous amniotic bands during intrauterine life. It can be seen in infants without any known genetic mutations. Band formation most frequently affects the distal segments, including the hand. Here, we report a case of a neonate who presented with multiple congenital abnormalities and clinical features that suggest the Amniotic Band Syndrome. It was delivered by a 17-year-old female patient at 28 weeks period of gestation, who had a medical abortion